Role of a 49 kDa Trypanosoma cruzi Mucin-Associated Surface Protein (MASP49) during the Infection Process and Identification of a Mammalian Cell Surface Receptor - Bertha Espinoza; Ignacio Martínez; María Luisa Martínez-Velasco; Miriam Rodríguez-Sosa; Augusto González-Canto; Alicia Vázquez-Mendoza; Luis I. Terrazas (Pathogens, 2023)
Trypanosoma cruzi is the etiologic agent of Chagas disease, a parasitic disease of great medical importance on the American continent. Trypomastigote infection’s initial step in a mammalian host is vital for the parasite’s life cycle. A trypomastigote’s surface presents many molecules, some of which have been proposed to be involved in the infection process, including a glycoprotein family called mucin-associated surface proteins (MASPs). This work describes a 49-kDa molecule (MASP49) that belongs to this family and is expressed mainly on the surfaces of amastigotes and trypomastigotes but can be found in extracts and the membrane-enriched fractions of epimastigotes. This protein is partially GPI-anchored to the surface and has a role during the internalization process, since its blockade with specific antibodies decreases parasite entry into Vero cells by 62%. This work shows that MASP49 binds to peritoneal macrophages and rat cardiomyocytes, undergoes glycosylation via galactose N-acetylgalactosamine, and can attach to the macrophage murine C-type lectin receptor (mMGL). These results suggest that MASP49 can be considered a virulence factor in T. cruzi, and a better understanding of its role in the infection process is necessary.